Petrographic of limestone cultural heritage as the basis of a methodology to rock replacement and masonry assessment: Cartagena de indias case of study. (December 2019) - Saba, M.; Hernandez-Romero, L.N.; Lizarazo-Marriaga, J.; Quiñones-Bolaños, E.E.
Abstract: Cultural heritage assessment and restoration around the word is an issue of main interest, in which destructive and non-destructive tests are usually undertaken to make diagnosis and evaluate material mechanical properties. Since interventions are often limited due to high costs, lack of highly specialized staff and even excessive caution of the competent authorities, it is common to have a lack of information about the cultural heritage material mechanical properties, with a consequent uncertainty about the adequate rock replacement and their masonry mechanical strength. In this perspective, the present research has taken as a case of study the defensive wall of Cartagena de Indias (UNESCO cultural heritage since 1984), introducing a petrographically based approach comparing fifteen limestones samples from five quarries and twelve structure samples. Firstly, is proposed a further step on improving the selecting rock criterion for replacement, identifying the main structure and quarry rock petrographical parameters, Bioclasts, Porosity, and Sparry Cement, and presenting a pyramidal scheme to be used in the replacement process. Subsequently, a new indicator was introduced for all rocks, and related to quarry rock uniaxial compressive strength (UCSR ), identifying thus the possible structure UCSR range. Finally, knowing UCSR range, the uniaxial masonry mechanical strength range (UCSM ) for the study case is calculated by referring to the 2018 Italian Technical Standard (NTC, 2018 [1]).